Diplomasi Kesehatan Global Dalam Penanganan Krisis MPOX Di Republik Demokratik Kongo OleH WHO Tahun 2022 – 2024 - Rahmawati, Sherly Widya; Ramadani, Nuri Salsa Bella (Universitas Pahlawan Tuanku Tambusai, 2026)
The Mpox (Monkeypox) outbreak represents a global health threat that transcends national borders and directly affects human security. The Democratic Republic of the Congo, as an endemic region, experienced a significant increase in Mpox cases during the 2022–2024 period, prompting active involvement from the World Health Organization (WHO). This study aims to analyze the role of WHO in global health diplomacy in addressing the Mpox crisis in the Democratic Republic of the Congo through the perspective of soft power diplomacy. The research employs a qualitative descriptive method using secondary data derived from WHO reports, academic journals, and relevant official documents. The findings indicate that WHO acts as a central actor through international coordination, the declaration of Public Health Emergency of International Concern (PHEIC), strengthening national health systems, and ensuring equitable distribution of vaccines and technical assistance. These efforts reflect the practice of global health diplomacy based on legitimacy, trust, and international cooperation.